Mitigating climate change impacts on West African rice yields: evaluating APSIM-ORYZA and management practices - Guidigan, M. L. G.; Dossou-Yovo, E. R.; Ra-danielson, A. M.; Akpoti, Komlavi; Tapily, A.; Iboko, M. P.; Balogun, A. A. (Wiley, 2025)
Rice (Oryza sativa) demand in sub-Saharan Africa is projected to rise by 12 million tonnes between 2021 and 2026. However, climate change poses a significant challenge to achieving rice self-sufficiency in the region. This study assessed the impact of climate change on rice yield and evaluated management practices to reduce associated yield losses in the derived savannah agroecological zone of West Africa. Field experiments were conducted on 22 farmers' fields across two irrigated schemes in central Cote d'Ivoire. Data on soil properties, weather, management practices, and rice yield was used to calibrate and validate the integrated model combining APSIM and ORYZA 2000 model. Future climate impacts were evaluated using bias-corrected data from RCP 4.5 and RCP 8.5 (where RCP is representation concentration pathway) scenarios. The model performed satisfactorily, with R2 values between 0.8 and 1, RMSE ranging from 0 to 5 t ha−1, and Nash–Sutcliffe Efficiency from 0.99 to 1. Projections indicated rice yield reduction of 82% and 77% by 2070–2100, under RCP 4.5 and RCP 8.5, respectively, compared to the 2019 baseline. Alternative management practices, including manure application at 3 Mg ha−1, rice straw mulching at 3 Mg ha−1, and nitrogen fertilizer at 180 kg ha−1, mitigated yield losses and even increased yield under climate change. These findings suggest that while climate change will substantially reduce irrigated rice yield, implementing improved management practices can enhance rice productivity and support food security in West Africa's derived savannah zone.